Role of magnetic field on blood flow with suspended silver nano particles through stenosed artery - M. Shiva Krishna,; Dr. P Maddileti, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The study of magnetic effects on silver nanoparticles suspended in the base fluid passing through an artery with overlapping stenosis is the focus of this publication. The study of magnetic effects on silver nanoparticles suspended in the base fluid passing through an artery with overlapping stenosis is the focus of this publication. A blood vessel with minor stenosis approximations is the subject of the study. Exact solutions for temperature, velocity, and flow resistance are found by solving the governing equations. The graphs have been used to study the effects of different parameters on the flow. According to the data taken into consideration, silver nanoparticles are effective at lowering the hemodynamics of stenosis and may have uses in biomedicine. According to the results, nanoparticles can be used as medicine carriers to reduce the negative effects of blood flow resistance